1991
DOI: 10.1111/j.1399-6576.1991.tb03364.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous morphine and oxycodone for pain after abdominal surgery

Abstract: Intravenous morphine and oxycodone were given double blind in doses of 0.05 mg/kg after major abdominal surgery to 39 patients. The dosing interval was 5 min, until the patient did not want any further analgesics. Less oxycodone was needed than morphine, both to achieve the "first state of pain relief" (13.2 mg vs. 24.9 mg) and during the whole 2-h study period (21.8 mg vs. 34.2 mg). The "first state of pain relief" was achieved faster (28 min vs. 46 min) and lasted longer (39 min vs. 27 min) with oxycodone th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
102
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 12 publications
10
102
0
Order By: Relevance
“…The study was carried out at about 13 h after surgery, as general anaesthesia may interfere with the pharmacokinetics of many drugs. The present results are in agreement with our previous findings demonstrating that the duration of the analgesic effect of intravenous oxycodone after abdominal surgery is longer than that of intravenous morphine (Kalso et al, 1991). It has been suggested that some of the analgesic effect of oxycodone might be due to its active metabolites (Kalso et al, 1990).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The study was carried out at about 13 h after surgery, as general anaesthesia may interfere with the pharmacokinetics of many drugs. The present results are in agreement with our previous findings demonstrating that the duration of the analgesic effect of intravenous oxycodone after abdominal surgery is longer than that of intravenous morphine (Kalso et al, 1991). It has been suggested that some of the analgesic effect of oxycodone might be due to its active metabolites (Kalso et al, 1990).…”
Section: Discussionsupporting
confidence: 83%
“…Oxycodone (14-hydroxy-7,8-dihydrocodeinone) is a semisynthetic opioid, with effects similar to those of morphine (Kalso et al, 1990(Kalso et al, , 1991Saarialho-Kere et al, 1989). Noroxycodone (Weinstein & Gaylord, 1979) and oxymorphone (Baselt & Stewart, 1978) are thought to be the main metabolites of oxycodone in man.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that oxycodone provides ef cient pain relief in acute postoperative pain (5) and in chronic pain (6). Oxymorphone, an active metabolite of oxycodone, is formed in the liver in an O-demethylation reaction, mediated by the enzyme CYP2D6 (7).…”
Section: Original Articlementioning
confidence: 99%
“…Numerous studies have suggested that IV oxycodone is an effective treatment for acute postoperative pain [16,17]. Furthermore, determination of the proper dosage regimen of oxycodone is important for effective pain control.…”
mentioning
confidence: 99%
“…Oxycodone is an effective analgesic agent for visceral pain and somatic pain, but studies to date have shown that it is more effective for visceral pain [7][8][9]27]. Likewise, pain after abdominal surgery is controlled by similar or smaller amounts of oxycodone compared with the equipotent ratio of morphine or fentanyl [16][17][18][19][20][21][22]. Therefore, in somatic pain such as pain after orthopedic surgery, the amount of oxycodone should be higher than the dose used for visceral pain.…”
mentioning
confidence: 99%